Complex Relationships Among Masculine Norms and Health/Well-Being Outcomes: Correlation Patterns of the Conformity to Masculine Norms Inventory Subscales. Issue 2 (March 2018) - Gerdes, Zachary T.; Levant, Ronald F.
The Conformity to Masculine Norms Inventory (CMNI) is a widely used multidimensional scale. Studies using the CMNI most often report only total scale scores, which are predominantly associated with negative outcomes. Various studies since the CMNI's inception in 2003 using subscales have reported both positive and negative outcomes. The current content analysis examined studies ( N = 17) correlating the 11 subscales with 63 criterion variables across 7 categories. Most findings were consistent with past research using total scale scores that reported negative outcomes. For example, conformity to masculine norms has been inversely related to help-seeking and positively correlated with concerning health variables, such as substance use. Nonetheless, past reliance on total scores has obscured the complexity of associations with the CMNI in that 30% of the findings in the present study reflected positive outcomes, particularly for health promotion. Subscales differed in their relationships with various outcomes: for one subscale they were predominantly positive, but six others were mostly negative. The situational and contextual implications of conformity to masculine norms and their relationships to positive and negative outcomes are discussed.